Partial Solidification Ejection Criteria for Injection Molding Production to Reduce Cycle Time. (April 2022) - Fu, Junyu; Liu, Jikai; Quan, Long; Ma, Yongsheng
Highlights: continued a recently reported work suggesting to achieve a dedicate optimum in-mold cooling time by taking care of both quality and productivity criteria simultaneously proposed a new ejection criteria model based on a recently published concept of partial solidification for early ejection in plastic part molding overcome the traditional over conservative theoretical ejection criteria for plastic part molding investigated the general time determination model targeting to significant reduced cycle times used a real industrial case study to show the procedure and its validation concluded that with the new criteria, the cycle time could be significantly reduced if the plastic parts are ejected earlier with qualified and controlled partial solidification Abstract: Productivity is essential in the injection molding process, especially for plastic parts featuring thick walls. However, for this process, product elastic and plastic deformations after in-mold cooling impose severe constraints on productivity enhancement. Due to the complexity of the molding process, producing high-quality plastic parts in less cycle time is still difficult even with the help of advanced molding simulation packages. The authors propose a new ejection criteria model based on a recently published concept of partial solidification for early ejection in plastic part molding and investigate the general time determination model targeting to reduce the cycle time tremendously. A real industrial case study has been provided to show the procedure and its verification. Compared to the traditional ejection criterion which the plastic parts need to be fully solidified by in-mold cooling, with the new criteria, the cycle time could be significantly reduced if the plastic parts are ejected earlier with qualified and controlled partial solidification.